CI-property for the group (ℤp)² × ℤq × ℤr - Ali, E.; Hassoon, A. (Algebra and Discrete Mathematics, 2019)
In this paper we prove that the group (ℤp)² × ℤq × ℤr is CI-group, where p, q, r are primes such that q and r divide p − 1, and r divides q − 1.